Colombia : Policy Strategy for Public Financial Management of Natural Disaster Risk - World Bank Group (2016)
Disasters resulting from natural hazards represent an important challenge for Colombia’s fiscal sustainability and stability. Colombia is one of the countries with the highest recurrence rate of disasters caused by natural hazards in Latin America (see the Annex)1. As the country’s population and economy continue to grow, so will the economic losses resulting from such events, an average of 600 disaster events of which is reported per year2. Colombia’s rate of economic growth is increasing the base of assets exposed to disaster risks, which may lead to significant increases in losses, particularly if investments in new assets are not accompanied by plans for mitigating disaster risk. The Government of Colombia (GoC) recognizes the importance of mitigating these events and has taken several steps to mainstream disaster risk management into its policy and programs, as evinced by the National Development Plan ‘2014-2018’, ‘all for a New Country’. The MHCP is committed to developing strategies for reducing its contingent liabilities in relation to disasters and to managing the fiscal risk resulting from these events. This document presents the priority policy objectives that have been established to assess, reduce, and manage fiscal risk due to natural disasters. It also describes the MHCP’s efforts to progress its policy objectives in the long term. These policy objectives represent the MHCP’s ex ante policy framework regarding management of financial and fiscal disaster risk. The MHCP identifies three priority policy objectives in order to strengthen management of the Government’s contingent liabilities and thus support the goal of achieving macroeconomic stability and fiscal balance. The policy objectives are: (i) identification and understanding of fiscal risk due to disasters; (ii) financial management of natural disaster risk, including the implementation of innovative financial instruments; and (iii) catastrophe risk insurance for public assets.